Prevalence and Predictors of Leg Cramps in the Third Trimester of Pregnancy: A Cross-Sectional Study - Abandeh A; Sindiani A; Nazzal MS; Almasri NA; Megdadi A; Morris L; Alshdaifat E; Kanaan SF (Dove Medical Press, 2024)
Ala'a Abandeh,1 Amer Sindiani,2 Mohammad S Nazzal,1 Nihad A Almasri,3 Afnan Megdadi,2 Linzette Morris,4 Eman Alshdaifat,5 Saddam F Kanaan4 1Department of Rehabilitation Sciences, Jordan University of Science and Technology, Irbid, Jordan; 2Department of Obstetrics and Gynecology, Jordan University of Science and Technology, Irbid, Jordan; 3Department of Physical Therapy, The University of Jordan, Amman, Jordan; 4Department of Rehabilitation Sciences, College of Health Sciences, QU Health, Qatar University, Doha, Qatar; 5Department of Obstetrics and Gynecology, Faculty of Medicine, Yarmouk University, Irbid, JordanCorrespondence: Saddam F Kanaan, Department of Rehabilitation Sciences, College of Health Sciences, QU Health, Qatar University, P.O. Box: 2713, 1st Floor, Building I06 Ibn Bitar, Doha, Qatar, Email saddam@qu.edu.qaObjective: This study aimed to estimate the prevalence and determine predictors of leg cramps among pregnant women in their third trimester.Methods: A sample of pregnant women in their third trimester who routinely visited local clinics in Jordan was recruited. Participants completed a socio-demographic and clinical characteristics questionnaire, the numeric pain rating scale (NPRS) for leg cramp pain intensity, the Arabic version of the Pregnant Physical Activity Questionnaire (PPAQ), the Nordic Musculoskeletal Questionnaire (NMQ), Short Form Health Survey (SF-12), Pittsburgh Sleep Quality Index (PSQI), and Hospital Anxiety and Depression Scale (HADS). In addition, magnesium (Mg) and calcium (Ca) serum levels were examined. Logistic regression analyses were used to identify predictors of leg cramps occurrence. A linear regression model was used to investigate predictors of leg cramps pain intensity among pregnant women who reported leg cramps.Results: Two hundred and five (n=205) pregnant women completed the study. The estimated prevalence of leg cramps was 58%. Logistic regression results showed that not receiving assistance with housework (OR 0.46, p=0.025), progress in the number of gestational weeks (OR 1.10, p=0.021), the number of previous pregnancies (OR 1.21, p=0.049), having leg swelling (OR 2.28, p=0.019), and having gastrointestinal (GIT) problems (OR 2.12, P=0.046) were associated with a higher odds of leg cramps occurrence. In the subsample with pregnant women with leg cramps, linear regression results showed that pregnant women with high school education versus elementary school (β=0.70, p=0.012), number of working hours (β=0.11, p=0.010), using vitamins supplements (β=− 1.70, p=0.043), having diabetes after pregnancy (β=1.05, p=0.036), having sciatica (β=0.58, p=0.028), having hip pain (β =− .33, p=0.029), and higher PSQI total score (β=0.09, p=0.020) were the significant predictors of leg cramp pain intensity.Conclusion: Many health-related conditions, as well as work and home-related work characteristics, may be considered risk factors for the occurrence of leg cramps and increased leg cramps pain intensity in pregnancy.Keywords: Leg cramps, pregnancy, prevalence, third trimester